Paediatric Contact Lens Fitting During COVID-19 - Bhattarai, Sanjeev (Medical Journal of Shree Birendra Hospital, 2022)
The COVID-19 pandemic which has swept the world since the start of 2020 is impacting day to day lives including contact lens wear too. Though the number of cases and deaths is growing continuously, the researchers have found no relationship between the contact lens use and COVID infection. There are specific eye disorders in children who require contact lens fitting rather than dispensing spectacles which include monocular paediatric aphakia, irregular astigmatism, anisometropia, unilateral ametropia, post trauma, aniridia, albinism, high refractive errors etc. So COVID-19 should not be a hindering factor for the fitting and assessment of contact lenses in children as till now SARS-CoV-2 viruses are rarely found in the tears of patients who have tested positive for the disease.